Influence of acidaemia and hypoxaemia on CVVH haemocompatibility in a porcine model - Bedarf, Janis Rebecca; Ruß, Martin; Ott, Sascha; Keckel, Tobias; Kirschfink, Michael; Unger, Juliane K. (Nephrology, dialysis, transplantation, 2010)
Background. Reduced haemocompatibility and early filter failure during continuous venovenous haemofiltration (CVVH) can be attributed to various aspects from filter engineering to rheological problems. Still, little is known about the impact of acidaemia and hypoxaemia on the haemocompatibility of a CVVH. In a porcine model, we investigated blood and coagulation parameters, filter performance and blockage of filter capillaries to assess the impact of acidaemia and hypoxaemia on haemocompatibility.Methods. Pigs were assigned to three groups (n = 6). One group received mixed acidaemia (pH 7.2) by acid infusion (0.2 M of lactic acid and 0.2 M HCl diluted in normal saline) and low tidal volume ventilation (6-8 mL/kg−1), one group underwent an additional hypoxaemia (pH 7.2; PaO2 < 70 mmHg) and another was treated with normal saline and normoventilation (control group; pH 7.4). To accelerate biocompatibility reactions, CVVH was operated with reinfusion of the filtrate to the venous line for 3 h based on standardized heparinization.Results. Acidaemia led to a contradictory pattern with respect to prothrombin time (prolongation), activated partial thrombin time and activated clotting time (acceleration). In comparison to normal pH homeostasis, acidaemia led to increasing activation markers such as terminal complement complex marker sC5b-9, thrombin-anti-thrombin complexes (TAT) and D-dimers. Additional hypoxaemia intensified activation with regard to TAT and complement complex marker sC5b-9. Platelet counts suffered from acidaemia and a tendency for higher rates of blocked hollow fibres was found.Conclusion. Acidaemia led to deteriorated haemocompatibility reactions to a CVVH circuit. The coagulation pattern developed towards complications for the coagulatory state.
Gesehen am 03.01.2023